Financing the Gig Economy - BUCHAK, GREG (Journal of Finance, 2024)
ABSTRACT Unlike traditional firm production, gig economy workers provide their own physical capital. As a consequence, the low‐income households for whom gig economy opportunities are most valuable often borrow to participate. In the context of ride share, difference‐in‐difference analysis reveals increased vehicle purchases, borrowing, utilization, and employment around entry, but financially constrained individuals cannot participate. To assess the equilibrium importance of financing, I build and estimate a structural model of the gig economy. Access to finance proves critical for the gig economy's growth: without finance, equilibrium quantities would be 40% lower and prices 90% higher, and only higher‐income households could participate as drivers.